Analysis of hospital efficiency in Chile - Barahona-Urbina, Planck (2011)
Introduction: Data envelopment analysis (DEA) helps determining which of the regional hospitals have better relative performance and which could improve the use of resources. Objectives: To analyze, using data envelopment analysis (DEA), hospitals technical efficiency in Chile. Design: Non parametric analysis. Setting: Chile’s Regional Public Hospitals. Interventions: Application of DEA to determine the efficiency of health establishments. Materials: Data for the period 1997-2006 of 190 public hospitals of different levels of expertise of the twelve regions of the country and the Metropolitan Region. Hospital and medical staff activity data have been identified -doctors, nurses, midwives, beds available as inputs and hospital discharge as output. Main outcome measures: Hospitals efficiency. Results: In 1997 regions IV, VII, VIII and IX hospitals were classified as technically efficient, that is, have made adequate use of their resources. Conclusions: In the ten-year study, 1997-2006, only in 1997 four Chile regions were efficient. Regional hospitals should reduce their inputs an average of 10% in order to stand on the efficient frontier. DEA is a good tool to measure efficiency and evaluate results of management.